2020
DOI: 10.1007/s10389-020-01393-x
|View full text |Cite
|
Sign up to set email alerts
|

Sources of information in times of health crisis: evidence from Turkey during COVID-19

Abstract: Aim Media as a source of information can shape public opinion regarding the COVID-19 response. Identifying how and where people seek information during the COVID-19 outbreak is vital to convey the most effective message about managing the COVID-19 crisis. The purpose of this study was to determine the sources of information and investigate the role of various demographic factors-age, gender, educational attainment and perceived economic level-on sources of information. Subject and methods An online survey (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 16 publications
1
29
0
3
Order By: Relevance
“…We consider that this temporal stability also indicates a high level of reliability of the results. Salimi et al [ 37 ] proposed that education-related differences in knowledge may be related to their finding that individuals with lower levels of education relied more on social media and less on public health resources to gain COVID-19-related information (see also [ 66 ]). The fact that misinformation about COVID-19 is widespread in social media [ 67 , 68 ] could be relevant to this finding.…”
Section: Discussionmentioning
confidence: 99%
“…We consider that this temporal stability also indicates a high level of reliability of the results. Salimi et al [ 37 ] proposed that education-related differences in knowledge may be related to their finding that individuals with lower levels of education relied more on social media and less on public health resources to gain COVID-19-related information (see also [ 66 ]). The fact that misinformation about COVID-19 is widespread in social media [ 67 , 68 ] could be relevant to this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies identified the most-used sources of health information during the pandemic to be online journalism, and social media. 3 , 4 These online sources reportedly aggravated the stress levels of their users. 4 Although the use of internet sources for health-risk information increased during the severe acute respiratory syndrome (SARS) and influenza A virus (H1N1) epidemics, it was not as high as speculated (25% and 56%, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…Before the pandemic, however, all social media platforms were available for all age groups; but they were mostly used by younger generation and mainly for pleasure. 1 , 3 Additionally, the public relays heavily on watching news reported on traditional TV; and they usually use social media and other platforms for surfing and browsing. 1 , 4 When it comes to finding important information related to health issues, they seek such information from health websites but not the social media platforms; 1 , 2 even though social media platforms are more accessible and are available at any time where users can access any health program at any time compared to traditional sources of information.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the fundamental factors of this development is the opportunities provided by digital tehcnologies, computer, internet and social networking sites and the quick and easy access to the above-mentioned services, and separation-individuation of people from others can be effective today. Therefore, it is more possible that individuals may benefit from infinite number of services such as communication, health, education, game, and self-realization Çiçek & Aslan, 2019;Geçer, Yıldırım & Akgül, 2020;Taş, 2019). Individuals are aware of reaching to these services through mass communication tools in general through internet use, particularly by using their smartphones.…”
Section: Introductionmentioning
confidence: 99%